ON PARANORMED I-CONVERGENT SEQUENCE SPACES OF INTERVAL NUMBERS - Khan, V. A.; Shafiq, M.; Ebadullah, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
In this article we introduce and study the paranormed I-convergent sequence spaces $\mathcal{C}^{I}(\mathcal{\bar{A}},p)$, $\mathcal{C} ^{I}_{0}(\mathcal{\bar{A}},p)$, $\mathcal{M}^{I}_{\mathcal{C}}(\mathcal{\bar{A}},p)$ and $\mathcal{M}^{I}_{\mathcal{C_{°}}}(\mathcal{\bar{A}},p)$ on the sequence of interval numbers with the help of a bounded sequence $p=(p_k)$ of strictly positive real numbers. We study some topological and algebraic properties and some inclusion relations on these spaces.